2019
DOI: 10.4103/ua.ua_36_18
|View full text |Cite
|
Sign up to set email alerts
|

Microdissection testicular sperm extraction: Overall results and impact of preoperative testosterone level on sperm retrieval rate in patients with nonobstructive azoospermia

Abstract: Objective: The main objective is to review the overall result and impact of preoperative testosterone level on sperm retrieval rate (SRR) by microdissection testicular sperm extraction (micro-TESE) in patients with nonobstructive azoospermia (NOA). Materials and Methods: We retrospectively reviewed the files of patients who underwent micro-TESE for NOA from August 2013 to December 2014. All patients were evaluated with history, physical examination, and hormonal assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The situation is quite different for the predictive role of serum T on the chances of sperm retrieval, since studies in the field have reported conflicting results. We were able to individuate 14 studies [29][30][31][32][33][34][35][36][37][38][39][40][41][42] who clearly reported the relationship between serum T levels and sperm retrieval rates (SRR) (Table 1). Studies differed for study design, inclusion criteria, and patients' characteristics.…”
Section: Relationship Between Serum Hormones Levels and Sperm Retrievalmentioning
confidence: 99%
See 1 more Smart Citation
“…The situation is quite different for the predictive role of serum T on the chances of sperm retrieval, since studies in the field have reported conflicting results. We were able to individuate 14 studies [29][30][31][32][33][34][35][36][37][38][39][40][41][42] who clearly reported the relationship between serum T levels and sperm retrieval rates (SRR) (Table 1). Studies differed for study design, inclusion criteria, and patients' characteristics.…”
Section: Relationship Between Serum Hormones Levels and Sperm Retrievalmentioning
confidence: 99%
“…Seven studies included patients with subnormal presurgical T levels, and six of them [34,37,38,[40][41][42] provided the sperm retrieval rates in patients with low vs. normal T levels. We pooled these latter data to compute the resulting odds ratio (OR), using random-effects models to comply with the high heterogeneity in study design, as detected by I 2 and by Cochran's Q. Computations and forest plot were obtained using Review Manager (RevMan, Version 5.3.…”
Section: Relationship Between Serum Hormones Levels and Sperm Retrievalmentioning
confidence: 99%
“…Subsequently, Mehmood et al. 61 found a significant correlation between preoperative testosterone levels and the SRR of MD-TESE. Althakafi et al.…”
Section: Factors Predicting the Srr In Patients With Noa Before Surgerymentioning
confidence: 97%
“…Kizilkan et al evaluated 860 patients and found that T levels were predictive of SSR in univariate, but not in multivariate, logistic regression [ 20 ]. On the other hand, Mehmood et al and Çayan et al, evaluating 264 and 327 patients respectively, found that SRR was significantly lower in men with low baseline T levels compared to those with normal baseline T levels (40.6 vs. 57.25, p = 0.0068, and 40.5% vs. 65.9%, p < 0.0001 respectively) [ 15 , 45 ]. Accumulating evidence suggests that higher baseline T levels may be associated with a higher probability of SSR in men with KS [ 26 , 34 ].…”
Section: Hormonal Parametersmentioning
confidence: 99%